Empirical typology of injured athletes: psychological resources and risks - L. M. Dovzhik; G. N. Tikhonov; K. A. Bochaver (National Electronic Information Consortium (NEICON), 2020)
Objective: to create a multi-factor predictive empirical model of athletic injury experience and coping behavior, taking into account the coping skills, emotional state, gender, age. Materials and methods: 227 athletes of various sports were examined. Questionnaires assessed the skills and strategies of coping, emotional state, subjective well-being, the level of resilience. Statistical processing was performed using the method of Bayesian regression-factor analysis. Results: six types of athletes were identified and described in accordance with their strategies to overcome stress, well-being and affective attitudes towards injury as a life event. The presented model has a high validity and allows analyzing of mental resources and risks of the injured athlete. Conclusions: in accordance with the results of the initial testing and interview with the injured athlete, it is possible to present the main personal risks for successful stress management and rehabilitation and to optimize the psychological support program.